2016
DOI: 10.4028/www.scientific.net/amm.839.81
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Biodiesel Prices in Thailand

Abstract: Biodiesel is a diesel equivalent fuel produced from biological feed stocks, acting as a substitute for petroleum or fossil diesel. Biodiesel production in Thailand began in 2005, with prices stabilizing after 2008. Biodiesel, along with other biofuels, plays a role in Thailand’s Alternative Energy Development Plan (AEDP). The purpose of this study is to examine factors in the Thai biodiesel prices (2009-2014). The study assessed factors in downstream biodiesel prices at consumer locations like gas stations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The most significant factor was the ex-refinery price, while the least was the marketing margin. The study also showed that while biodiesel's consumer price in Thailand can be mostly attributed to cost factors, there was some unexplained variance in price (Laung-iem and Thanarak, 2016).…”
Section: Causal Model or Regression Analysismentioning
confidence: 81%
“…The most significant factor was the ex-refinery price, while the least was the marketing margin. The study also showed that while biodiesel's consumer price in Thailand can be mostly attributed to cost factors, there was some unexplained variance in price (Laung-iem and Thanarak, 2016).…”
Section: Causal Model or Regression Analysismentioning
confidence: 81%